Rgec (Risk Profile, Good Corporate Governance, Earnings, Capital) Study of State-Owned Companies in the Banking Sector Listed on the Indonesian Stock Exchange 2018-2020 - Ghali Setya Nugroho; Elwisam Elwisam; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This research aims to analyze the financial performance of commercial banks (BNI, BRI, BTN and Banque Mandiri) for the 2012-2013 period using RGEC (Risk Profile, Good corporate governance, Capital). Analytical tools used is the RGEC method (Risk Profile, GCG, Earnings, and Capital). Meanwhile method this research uses a descriptive method quantitative. The subject of this research are all commercial banks registered in the Bank Indonesia directory period annual report 2018 to 2020. Data collection techniques which used is technique documentation and technique literature. Results study show in a way whole performance finance Bank BUMN during 2018 - 2020 period in terms of risk profile, namely by analyzing credit risk which is represented by the NPL ratio is said to be good and from liquidity risk analysis which is represented by the LDR ratio can be said to be quite liquid. Meanwhile from In terms of Good Corporate Governance (GCG), the bank's performance is very good. As well as whole performance finance from facet Profitability (Earnings) that is with analyze the ROA ratio or profit based on assets and the NIM ratio or Management's ability to control bank costs is said to be good. And in a way whole performance finance from facet capital with analyze the ratio of capital to assets weighted according to risk (RWA) which is represented by calculating the CAR ratio (Capital Adequacy Ratio) Bank said OK.